Use of the ADAPTE method to develop a clinical guideline for the improvement of psychoses and schizophrenia care: Example of involvement and participation of patients and family caregivers. (23rd February 2021) - Hurtado, María M.; Quemada, Casta; García‐Herrera, José María; Morales‐Asencio, José Miguel
Abstract: Introduction: The aim of this study is to analyse different ways of participation during the development of a clinical guideline to improve the early detection of psychosis and to deploy a comprehensive treatment plan to improve prognosis and social integration. Materials and method: The clinical guideline was developed using the ADAPTE method with the participation of 40 authors and 80 external reviewers. The process was divided into three major phases: set up, adaptation and finalization. During adaptation and completion, a total of 44 patients and 18 family caregivers were involved. Results and conclusions: The different roles assumed by the patients and their family caregivers were described, depending on the panel in which they participated, with diverse grades of complexity: a user as author, integration of the results of qualitative research with the participation of local users and family caregivers, 13 users as individual external reviewers and the participation of users and caregiver organizations in the external review. In the guideline, contributions from patients during the qualitative research were included in an innovative way, placing them just behind the recommendations. On the other hand, the results of the family caregivers' study were included in a specific area of uncertainty. Further, the expressed point of view was considered as the collective demands of users and family caregivers' organizations in the cost‐benefit analysis made by the organizing committee. There were diverse ways to conduct direct patient participation during the guideline development, ensuring that their individual experiences contributed significantly to the final version.